Material extrusion-based printing optimization of recycled HDPE filaments made from used milk jugs - Teng, Phillis Soek Po (2025)
Fused deposition modeling printing is a material extrusion (MEX) process that has gained popularity over the years due to its increased affordability and greater versatility. There is a wide variety of MEX printing technologies and a broad spectrum of materials that can be 3D printed, ranging from metallic to non-metallic materials. MEX has emerged as the most common technology in consumer-grade, desktop 3D printers for printing thermoplastics, such as acrylonitrile butadiene styrene (ABS) and polylactic acid. High-density polyethylene (HDPE) is a widely used thermoplastic material for product packaging. The sheer availability of recyclable or recycled HDPE (rHDPE) from used packaging has led to efforts to apply it in MEX printing. However, rHDPE presents challenges as a filament material, including issues such as part detachment from the print bed and high warpage. The focus of this study is to determine the optimal conditions that can mitigate, if not eliminate, the print bed adhesion problems associated with printing rHDPE filaments. This was achieved by conducting a series of tests to address these challenges, including part removability relating to the shear strength of print bed adhesion to identify the necessary range of print bed adhesion and corresponding parameters.